Pengembangan Aplikasi Berbasis Android Pada Pembelajaran Matematika Materi Pecahan Kelas V SD Menggunakan Smart App Creator - Andyan Anditya; Suyitno Suyitno; Adin Fauzi (Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
In this research, researchers developed innovations in the use of technology-based learning media in mathematics learning. Based on searching for problems in the field, researchers found the monotony of the learning process and the lack of interest in mathematics learning, especially in class V fraction material. From the above problems, it is necessary to have learning media that can be interesting and fun for students. This research aims to determine the suitability and readability of students in the Smart App Creator mathematics learning media for class V elementary school fractions. The type of research used is Research and Development (RnD), which researchers have modified into 7 stages, namely: searching for potential and problems, data collection, product design, design validation, design revision, product testing, and product revision. In the research instrument, the researcher used a questionnaire, with test respondents on 2 class V teachers and 11 class V students. Data analysis techniques in this research used qualitative and quantitative. The results of the research developed by Android-based media applications in mathematics learning material for fractions in class V elementary school using Smart App Creator are in terms of material experts the percentage is 85.83% with a decent level of validity, in terms of media experts the percentage is 88.67% with a decent level of validity, in terms of linguist percentage 78.67% with a decent level of validity. In the media readability questionnaire, students got a percentage of 92.5% with a very decent level of validity.